2021
DOI: 10.1016/s1473-3099(20)30736-2
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal antibody and T cell responses in Ebola virus disease survivors and contacts: an observational cohort study

Abstract: Background The 2013-16 Ebola virus disease epidemic in west Africa caused international alarm due to its rapid and extensive spread resulting in a significant death toll and social unrest within the affected region. The large number of cases provided an opportunity to study the long-term kinetics of Zaire ebolavirus-specific immune response of survivors in addition to known contacts of those infected with the virus.Methods In this observational cohort study, we worked with leaders of Ebola virus disease surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…A surprising finding of this study is that a minority of household contacts also had polyfunctional antibody effector functions. Polyfunctional responses were more frequent in the contacts that presented two or more symptoms at the time of the outbreak, indicating that some of them might have a milder or subclinical form of the disease, as suggested by other studies (33)(34)(35). Alternatively, it has also been documented that EBOV seropositivity in parts of Africa, including Uganda, is associated with wild animals contacts (35)(36)(37), and thus this baseline seropositivity may also contribute to the Fc-mediated antibody effector response that we observed in some household contacts.…”
Section: Discussionsupporting
confidence: 60%
“…A surprising finding of this study is that a minority of household contacts also had polyfunctional antibody effector functions. Polyfunctional responses were more frequent in the contacts that presented two or more symptoms at the time of the outbreak, indicating that some of them might have a milder or subclinical form of the disease, as suggested by other studies (33)(34)(35). Alternatively, it has also been documented that EBOV seropositivity in parts of Africa, including Uganda, is associated with wild animals contacts (35)(36)(37), and thus this baseline seropositivity may also contribute to the Fc-mediated antibody effector response that we observed in some household contacts.…”
Section: Discussionsupporting
confidence: 60%
“…Both B cell-and T cell-mediated responses are believed to be correlates of protection against EBOV infection, as indicated by high levels of neutralizing antibodies and antiviral T cells in human EVD survivors [2,14,15,46,47]. On the other hand, lymphopenia is a characteristic of EVD [16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, infection of DCs results in reduced expression of costimulatory molecules and impaired antigen presentation which in turn disrupts the mobilization of adaptive immunity [10][11][12][13]. This includes T cell-mediated and humoral immunity, both which are critical for controlling infection and conferring vaccine-mediated protection [2,14,15]. Fatal EVD cases are associated with a robust and sustained adaptive systemic cytokine storm and dramatic loss of lymphocytes, while survivors show early control of innate and immune responses [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as already discussed, the passive infusion of neutralizing antibodies has shown efficacy in the treatment of EVD [ 99 ], reinforcing the importance of eliciting this sort of antibodies by vaccination ( Figure 2 ). Accordingly, previous results obtained with EBOV survivors showed that these individuals developed a strong neutralizing humoral response to EBOV GP [ 142 ] that can be higher than the humoral response observed in deceased patients [ 143 , 144 ].…”
Section: Vaccines For Ebov and For Sars-cov-2 Infectionmentioning
confidence: 99%